Clinical Imaging of Bone Microarchitecture with HR-pQCT - Nishiyama, Kyle K. (2013)
Osteoporosis, a disease characterized by loss of bone mass and structural deterioration, is currently diagnosed by dual-energy x-ray absorptiometry (DXA). However, DXA does not provide information about bone microstructure, which is a key determinant of bone strength. Recent advances in imaging permit the assessment of bone microstructure in vivo using high-resolution peripheral quantitative computed tomography (HR-pQCT). From these data, novel image processing techniques can be applied to characterize bone quality and strength. To date, most HR-pQCT studies are cross-sectional comparing subjects with and without fracture. These studies have shown that HR-pQCT is capable of discriminating fracture status independent of DXA. Recent longitudinal studies present new challenges in terms of analyzing the same region of interest and multisite calibrations. Careful application of analysis techniques and educated clinical interpretation of HR-pQCT results have improved our understanding of various bone-related diseases and will no doubt continue to do so in the future.